إسماعيل العربي مناضلا ومؤرخا 1919 – 1997م - شيماء رضواني; أسماء شادو; حليمة مسعي محمد (جامعة الوادي - University of Eloued, 2025)
"إسماعيل العربي، مُفكر، ومؤرخ، ومناضل وطني، إنخرط في النضال الوطني من خلال جمعية العلماء المسلمين حيث جمع بين النضال الثقافي والبحث الأكاديمي، فقد ساهم في الحفاظ على الهوية الوطنية الجزائرية وتعزيز الوعي التاريخي. عُرف بأعماله التاريخية الهامة فقد قدم للمكتبة الجامعية إنتاج أكاديمي متنوع في مختلف المجالات، متكون من 46 كتاب وعدة مقالات باللغات الثلاثة نتيجة لرصيده المتعدد الذي سمح له بأن يتولى مناصب تدريس في الجامعات الجزائرية والفرنسية وحتى المصرية. "Ismail AL-Larbi is a thinker, historian, and national activist. He became involved in the national struggle through the Association of Muslim Scholars, where he combined cultural activism with academic research. He contributed to preserving Algerian national identity and enhancing historical awareness. Known for his significant historical works, he contributed to the university library a diverse academic output in various fields, consisting of 46 books and several articles in three languages. His diverse background allowed him to hold teaching positions at Algerian, French, and even Egyptian universities. "
مذكرة ماستر قسم التاريخ تخصص المغرب العربي المعاصر
Keywords: إسماعيل العربي; الوعي التاريخي; إنتاج أكاديمي; نضال الثقافي.; Ismail Al-Arabi; historical awareness; academic production; cultural struggle.